2021
DOI: 10.3390/app11188526
|View full text |Cite
|
Sign up to set email alerts
|

An Analytical Study on the Pull-Out Strength of Anchor Bolts Embedded in Concrete Members by SPH Method

Abstract: As an important method for connecting structural members, anchor bolts have been installed in many situations. Therefore, accurate evaluation of the pull-out strength of anchor bolts has always been an important issue, considering the complicated actual installation conditions and the problem of aging deterioration of the structural members. In general, the patterns of pull-out failure of anchor bolts can be classified into three types: adhesion failure, cone failure, and bolt break. However, it sometimes show… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 25 publications
1
3
0
Order By: Relevance
“…However, due to the tiny space between the anchors, there was a superposition of the concrete cone failures, resulting in a complex double cone failure surface (Figures 13d, e, and f). Studies by Lu and Sonoda (2021) observed similar behavior. Additionally, the ultimate load values of the numerical models of the parametric study with edge and group effects were verified against the calculation model of the ACI 318 (2019) normative prescription.…”
Section: Edge and Group Effects On N Usupporting
confidence: 56%
“…However, due to the tiny space between the anchors, there was a superposition of the concrete cone failures, resulting in a complex double cone failure surface (Figures 13d, e, and f). Studies by Lu and Sonoda (2021) observed similar behavior. Additionally, the ultimate load values of the numerical models of the parametric study with edge and group effects were verified against the calculation model of the ACI 318 (2019) normative prescription.…”
Section: Edge and Group Effects On N Usupporting
confidence: 56%
“…There has been a growing interest in modeling the local interaction between anchors and soil with mesh-free techniques combined with a continuum mechanics approach, such as the Material Point Method (MPM) (Liang et al, 2021) and the Smoothed Particle Hydrodynamics (SPH) method (Woo et al, 2015;Wu et al, 2019;Lu and Sonoda, 2021). Other MPM applications include the simulation of avalanches (Vriend et al, 2013), the modeling of cone penetration in soils (Ceccato et al, 2017) and the design of locomotion systems in granular media (Ortiz et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the smoothed particle hydrodynamics (SPH) method developed by Gingold and Monaghan, and Lucy in 1977 [24,25], is a numerical technique and belongs to the category of mesh-free discretization techniques that could be used in continuum mechanics to simulate solid dynamics, including elasticity and plasticity [26]. Considering the advantage of SPH over FEM that it is easy to analyze the final fracture conditions accurately and realistically by taking advantage of the mesh-free method [27], SPH is often employed to analyze the impact behavior of structures [26,28].…”
Section: Introductionmentioning
confidence: 99%